The Wiley Blackwell companion to East and inner Asian Buddhism - Poceski, Mario (John Wiley & Sons Inc., 2014)
The Wiley Blackwell Companion to East and Inner Asian Buddhism combines outstanding contributions covering Buddhism as it developed and is practiced in this region. These newly-commissioned essays provide fresh scholarly perspectives on a wide range of concepts, texts, and practices. Offers a comprehensive and balanced survey of Buddhism within East and Central Asia, from the time of the Buddha through to the present dayProvides fresh perspectives on a wide range of concepts, texts, traditions, doctrines, practices, and institutions - on topics spanning gender roles.